New constraints for the alpine HP metamorphism of the Ios basement, Cyclades, Greece - PERRAKI, M.; MPOSKOS, E. (Bulletin of the Geological Society of Greece, 2001)
The pre-Alpine basement of the Ios Island involves large Variscan granitoid bodies intruded into metasediments that had already been metamorphosed under upper amphibolite facies conditions, as it is indicated by residual migmatitic textures and deformed muscovite pegmatites. The Alpine HP-metamorphism, documented on various cycladic islands, has, also, affected the basement rocks of Ios. Pressures of '25 Kbar and temperatures of '540 °C, are estimated for the Alpine HP event, applying the chloritoid-chlorite and garnetclinopyroxene geothermometers, and the garnet-phengite-omphacite and garnet-rutile-quartz-sphene-clinozoisite geobarometers. Garnet-hornblende geothermometry yielded temperatures of '520 °C and garnet-chlorite geothermobarometry yielded temperatures of 450 °C at 15 Kbar. This suggests that, at least the first stages of decompression were accompanied by cooling, indicating a rapid exhumation, related to tectonic processes.